Effect of cooking conditions on quality of sweetened adzuki an - Xinmiao, Yao; Shuwen, Lu; Xianzhe, Zheng; Jingkun, Sun; Chuanying, Ren; Zhang, Yinglei; Xuejun, Xie; Xiangdong, Sun (International Journal of Agricultural and Biological Engineering, 2014)
Abstract: To produce high sensory quality sweetened adzuki an, the effects of cooking conditions include cooking time, heating power, sugar soaking time and soaking liquid pH on textural properties and sensory scores were evaluated using central composite experimental method. Blanching treatment and sodium tripolyphosphate were adopted to improve the mouthfeel of the whole bean an product. Results showed that the optimal parameters were as follow: cooking time of 50 min, heating power of 1.1 kW, sugar soaking time of 2 h and soaking liquid pH of 8.0, which resulted in the highest sensory score of 89.6. In this study, the effectiveness of the method to process sweetened whole bean adzuki an was validated and a sensory evaluation method for whole grain adzuki an product was developed. Keywords: sweetened adzuki an, quality, cooking conditions, processing, sensory evaluation DOI: 10.3965/j.ijabe.20140704.015 Citation: Yao X M, Lu S W, Zheng X Z, Sun J K, Ren C Y, Zhang Y L, Xie X J, Sun X D. Effect of cooking conditions on quality of sweetened adzuki an. Int J Agric & Biol Eng, 2014; 7(4): 134-142.